2011
DOI: 10.1186/1756-0500-4-193
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of Hepatitis C among individuals presenting to HIV testing centers, Hawassa city, Southern Ethiopia

Abstract: BackgroundHepatitis C virus (HCV), either alone or in combination with Human Immunodeficiency virus (HIV), constitutes a major public health concern. This study was conducted to describe the prevalence and risk factors for HCV infection in people with and without HIV infection.MethodsBlood samples and data on socio-demographic and risk factors for HCV infection were collected from consecutive 400 HIV- positive and 400 HIV- negative individuals attending HIV testing centers in Hawassa city, from October to Dece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 18 publications
3
20
2
Order By: Relevance
“…This study is in agreement with previous studies conducted in Gondar among antenatal clinic attendees (7.3%) [29] , in Amhara and Tigray regions of Ethiopia -among blood donors (6.2%) [27] , in Kenya (6%) [32] and India (6.3%) among HIV infected patients [33] . However, the prevalence of HBsAg was found lower compared to the 10.9% in Gondar City among street dwellers [31] .…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…This study is in agreement with previous studies conducted in Gondar among antenatal clinic attendees (7.3%) [29] , in Amhara and Tigray regions of Ethiopia -among blood donors (6.2%) [27] , in Kenya (6%) [32] and India (6.3%) among HIV infected patients [33] . However, the prevalence of HBsAg was found lower compared to the 10.9% in Gondar City among street dwellers [31] .…”
Section: Discussionsupporting
confidence: 82%
“…On the other hand, previous studies conducted in Addis Ababa and Hawassa city had reported no significant association between HCV and blood transfusion history among HIV infected patients [26,27] . The difference might be due to patients infected with HIV have lower hemoglobin value probably requiring frequent blood transfusion without following good screening methods of blood donors such as ELISA technique and HCV RNA in the study area.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Ababa1658(4.8)[55]2006A. Ababa73450 (6.8)[66]2008Hawassa40042(10.5)[11]2011A. Ababa50018 (3.6)[53]2011Mekele17416(9.2)[12]2012D/ Tabour3955(1.3)[67]2013A.Ababa38725(6.5)[68]2013Gondar40022(5.5)[64]2013Bahirdar26959(21.9) a [100]2014Bahirdar25314(5.5)[69]Others b 2006Gondar4806 (1.3)[39]2006A.…”
Section: Resultsmentioning
confidence: 99%